2017
DOI: 10.5539/jms.v7n3p22
|View full text |Cite
|
Sign up to set email alerts
|

Regional Difference in the Organizational Commitment-Rewards Relationship in Vietnam

Abstract: This study investigates the relationship between rewards and the organizational commitment (OC) of 5,522 employees who work for 5 Japanese companies in Vietnam focusing on the difference between Red River Delta (Hanoi and surrounding provinces) and South East (Ho Chi Minh City and surrounding provinces). Hierarchical regression analysis revealed that co-worker support had stronger influence on OC in Red River Delta than in South East. On the other hand, benefit satisfaction had stronger influence on OC in Sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…Jones and Sloane ( 2009) suggested that regional differences affect the job satisfaction even in the same country. It is also suggested that organizational commitment may vary from a region to the other in the same country (Kokubun, 2017). In the light of these studies, the moderating effect of region on the surveyed relationships will be tested.…”
Section: Conceptual Relationships and Hypothesis Developmentmentioning
confidence: 99%
“…Jones and Sloane ( 2009) suggested that regional differences affect the job satisfaction even in the same country. It is also suggested that organizational commitment may vary from a region to the other in the same country (Kokubun, 2017). In the light of these studies, the moderating effect of region on the surveyed relationships will be tested.…”
Section: Conceptual Relationships and Hypothesis Developmentmentioning
confidence: 99%
“…Farklı bölgelerde yaşayanların aynı ülkede bile farklı iş tatmini seviyelerine sahip olabileceği (Jones & Sloane, 2009) ve aynı ülkedeki bölgesel farklılıkların örgütsel bağlılık üzerinde etkili olabileceği kanıtlanmıştır (Kokubun, 2017). Alas ve Edwards (2011), iş tatmini ve örgütsel bağlılığın kıtalardan etkilendiğini öne sürmüştür.…”
Section: Kavramsal İlişkiler Ve Hipotez Geliştirmeunclassified
“…Indeed, in previous empirical research in setting of Vietnam, OC was more correlated with extrinsic rewards among employees of more developed area while it was more correlated with social rewards among those of less developed area, indicating people tend to become more individualistic or less collectivistic and the nature of relationship between OC and rewards change accordingly (Kokubun, 2017d). Another study in setting of China showed that OC became more correlated with social rewards after the financial crises in 2008, indicating that employees became more collectivistic during the long lasting economic stagnation, which may be understood as the reversed phenomenon of the relationship between economic development and the OC-rewards link (Kokubun, 2017b).…”
Section: Comparative Importance Of Rewardsmentioning
confidence: 99%